A STUDY ON BLACKSMITHS OF NORTHERN TELANGANA AND THEIR ANNUAL FESTIVAL-MAMMAYEE - Vittal .S (EPRA International Journal of Multidisciplinary Research (IJMR), 2023)
The aim of the paper is to record the presence, lives and working practices of rural blacksmiths and descendants of iron smelters; and to study and document the Mammayee festival, which is the traditional annual rejuvenation festival of the blacksmith community of the region dedicated to their goddess, Mammayee. The data gathered during the field survey represents a valuable ethno-archaeological tool to study the effect of social organization, culture and tradition of the rural blacksmiths of the Telangana region and understand their approach to metals. Collecting ethnographic data in the field involved interviewing blacksmiths in their residences or work-spaces; Non-blacksmiths, including village elders, toddy tappers, owners of land containing slag or crucible heaps were also interviewed to gather knowledge or memory of past smelting as well as smithing. Topics asked include the blacksmithing tradition of his family and the village; memory about past smelting and smithing; kinds of tools produced or repaired; target market and clients of the manufactured products; remuneration system; source of raw materials; apprenticeship process and the future of traditional blacksmithing from their perspective. The detailed study of the annual festival of the blacksmiths was conducted by visiting the temples of their goddess Mammayee on the first day of the festival and interviewing blacksmiths about the preparation and ritual performances. The rituals were observed in four villages (Kalvala, Uploor, Ibrahimpatnam and Konasamudram).